The Relationship between Customer’s Personal Characteristics and Usage of Electronic Banking Services - Heidari, Aram; Asady, Nadia (Journal of University of Human Development, 2016)
Nowadays, data is the heart of business processes of small and large companies, such as retailers, communication, production, facilities, transportation, insurance, credit cards and banking. Hence, there is a need for a tool that can process stored data and provide users with the information obtained from this process. In this context, data mining is one of many scientific branches that in recent years has experienced a rapid expansion worldwide. Data mining is the process of discovering knowledge (that is) hidden in data, which by describing, explaining, predicting and controlling various phenomena, has a wide application in various fields. The main idea of ​​data mining is based on the fact that old data contain information that can be used in the future and will be valuable. The purpose of data mining is to find those patterns in existing data that make the needs, preferences and desires of the business clearer. Therefore, extracting the symptoms from useless things, i.e. identifying underlying patterns within seemingly random variables, is one of the important roles of data mining. The aim of this paper is to analyze the relationship between individual characteristics of the client and the use of electronic banking services (using data mining methods).